The experiences of redeployed educators from down-sized schools - Simeon Maile (Acta Academica, 2005)
The process of redeployment is viewed in this article from the perspective of the theory of managerialism in order to explain why educational institutions change. Redeployment is seen as part of the transformation process. Redeployment victims suffer a syndrome characterised by feelings of loss, anxiety, anger, insecurity, mistrust and stress. This syndrome is described by means of empirical data. The article compares arguments from theoretical propositions and integrates them with the data drawn from empirical investigation. While redeployment has succeeded in distributing educators across the education system, it has also brought misery to the careers of some educators, especially those who have experienced the process first-hand.